2019
DOI: 10.1111/liv.14265
|View full text |Cite
|
Sign up to set email alerts
|

Gene signature‐MELD score and alcohol relapse determine long‐term prognosis of patients with severe alcoholic hepatitis

Abstract: Background The gene‐signature‐model for end stage liver disease (gs‐MELD) score has been shown to be a strong predictor of 6‐month survival in severe alcoholic hepatitis (AH). Currently, only a few studies have evaluated the long‐term prognosis of patients with severe AH. Aim To assess the prognostic value of the gs‐MELD score at 5 years in patients with severe AH. Methods Forty‐eight consecutive patients with AH (25 males, median age 52 years [95% IC: 48‐56]) were included. Results The median gs‐MELD score wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…[26][27][28][29] Moreover, while scores of liver disease severity such as the MELD and Lille scores are prognostic of short-term mortality in patients with severe AH, alcohol relapse is a key factor of long-term mortality in this population. [7][8][9] The definition of abstinence varies in different studies. We defined abstinence as complete abstinence from alcohol within the year after liver biopsy without any relapse thereafter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28][29] Moreover, while scores of liver disease severity such as the MELD and Lille scores are prognostic of short-term mortality in patients with severe AH, alcohol relapse is a key factor of long-term mortality in this population. [7][8][9] The definition of abstinence varies in different studies. We defined abstinence as complete abstinence from alcohol within the year after liver biopsy without any relapse thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] It has been previously shown that severity scores, including the model for end-stage liver disease (MELD) and the Lille score, predict short-term mortality in patients with severe AH treated with corticosteroids and that alcohol abstinence is the main predictor of long-term survival. [7][8][9] Patients with AH and an mDF <32 have less than a 10% risk of 1-month mortality 3 and are typically not considered for specific therapy. However, the definition of AH severity is based on old studies and the evolution of non-severe forms of AH is still uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…9 Trépo and colleagues have taken up this challenge and have recently adopted the novel approach of determining outcomes in patients with severe AH utilizing transcriptome profiling. 10 In this issue of the journal the same authors, 11 having shown that the gs-MELD scoring system accurately predicts 90 and 180 day survival in patients with severe AH, now report data on the predictive validity of the score for determining long-term survival in the same population. This post-hoc analysis was undertaken using follow-up data from the 48 patients with severe AH who comprised the validation cohort in the index publication.…”
Section: Predicting Long-term Prognosis In Severe Alcoholic Hepatitismentioning
confidence: 99%
“…The work undertaken by this group 10,11 is an excellent example of how combining individual genetic expression data and clinically available routine variables can be used to build a prognostic score. A particular strength of the gs-MELD scoring system is that the prognostic information is available sufficiently early to be used to guide management and avoid use of medication which may cause adverse effects.…”
Section: Predicting Long-term Prognosis In Severe Alcoholic Hepatitismentioning
confidence: 99%
See 1 more Smart Citation